Comprehensive understanding of the roles of water molecules in aqueous Zn-ion batteries: from electrolytes to electrode materials. Issue 7 (19th May 2021) - Li, Ming; Li, Zilan; Wang, Xuanpeng; Meng, Jiashen; Liu, Xiong; Wu, Buke; Han, Chunhua; Mai, Liqiang
Abstract : This review summarizes the influences of water molecules during the energy storage process from the perspectives of the electrolyte, Zn anode, and cathode materials, including the basic theory, modification methods, and practical applications. Abstract : Benefiting from loose assembly conditions, a high level of safety and environmentally friendly characteristics, rechargeable aqueous Zn-ion batteries (AZIBs) have attracted significant attention. The electrochemical kinetics and performance of the AZIBs are greatly affected by water in electrolytes or electrode materials. The corrosion and passivation of the Zn electrode caused by the inevitable solvation process of water molecules can lead to the growth of dendrites, thus resulting in a limited cycle life. Moreover, water in the electrode material, whether in the form of structural water or co-intercalated hydrated cations, can greatly affect the electrochemical behavior due to its small size, high polarity and hydrogen bonding. Unlike previous reports, this review focuses on the roles of water molecules during electrochemical processes in AZIBs. We comprehensively summarize the influencing mechanisms of water molecules during the energy storage process from the perspectives of the electrolyte, Zn anode, and cathode materials, and further include the basic theory, modification methods, and practical applications. The mystery concerning the water molecules and the electrochemical performance of AZIBs is revealed herein, and we also propose novel insights and actionable methods regarding the potential future directions in the design of high-performance AZIBs.